The re-sequencing of complete chloroplast genome of Cinnamomum camphora (Lauraceae) from Quanzhou, China - Qiu, Meng-Yuan (Mitochondrial DNA B Resour, 2020)
Cinnamomum camphora is a precious species for its significance of timber. It is also the main component of the subtropical evergreen broad-leaved forest. We report a chloroplast genome of C. camphora from Quanzhou, China. The complete chloroplast genome is 152,730 bp in length consisting of a pair of inverted repeat (IR) regions of 19,968 bp, a small single-copy (SSC) region of 18,874 bp, and a large single-copy (LSC) region of 93,706 bp, respectively. The chloroplast genome encoded 116 genes, including 79 protein-coding genes, 36 tRNA genes, and eight rRNA genes. This result will provide useful genomic basis for the phylogenetic research of Lauraceae.